Holocene Paleoecology in the Neotropical Savannas of Northern South America (Llanos of the Orinoquia Ecoregion, Colombia and Venezuela): What Do We Know and on What Should We Focus in the Future? - Piraquive-Bermúdez, Daniela; Behling, Hermann (Frontiers in Ecology and Evolution, 2022)
We provide an overview of the Holocene paleoecology of the Llanos ecoregion. A region that captured the attention of researchers for more than 200 years, as it exhibits a high heterogeneity in landscapes and vegetation, where savanna and forest mosaics exist. Located in an area influenced by the seasonal migration of the Intertropical Convergence Zone, it provides a unique area for understanding long-term dynamics of climate, vegetation and human history. Twelve locations have been paleoecologically studied, showing general vegetation and climate changes trends since the Last Glacial Maximum (LGM). During LGM savanna herbs were dominant, indicating dry climatic conditions. The transition of the Holocene was characterized by a slight increase in forest taxa, suggesting a transition to a wetter climate. Between ~10000 and 7000 cal yr BP, grasslands were abundant, and few forest taxa, including Mauritia were also common but rare, pointing to a warm and humid climate. After ~7000 cal yr BP, the gallery forest started to expand, suggesting a change to a wetter climate. Mauritia palms increased markedly after 4000-3000 cal yr BP, possibly driven by higher mean annual precipitation and/or longer wet season. The start of human occupation remains unclear, but it has been linked to the time of expansion of Mauritia, a period in which fires, possibly of anthropogenic origin, were more frequent. To understand patterns of change in these ecosystems, it is necessary to improve the chronological control of the sediments in future studies and increase the resolution and proxies used to reconstruct their history.